2014
DOI: 10.1098/rspb.2013.2094
|View full text |Cite
|
Sign up to set email alerts
|

Meta-ecosystem dynamics and functioning on finite spatial networks

Abstract: The addition of spatial structure to ecological concepts and theories has spurred integration between sub-disciplines within ecology, including community and ecosystem ecology. However, the complexity of spatial models limits their implementation to idealized, regular landscapes. We present a model meta-ecosystem with finite and irregular spatial structure consisting of local nutrient-autotrophs-herbivores ecosystems connected through spatial flows of materials and organisms. We study the effect of spatial flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 40 publications
2
81
3
Order By: Relevance
“…We further illustrate that differences in the pattern of connections and initial conditions among communities lead to the emergence of a wide array of stable asynchronous dynamics, leading to substantial differences in the potential persistence of an unstable predator-prey interaction at both the regional metacommunity and local patch level, despite the otherwise strict homogeneity of our metacommunities in which each community is identical and connected to exactly four other community patches. Our study is the first to produce this range of dynamical variation as a result of such subtle changes in spatial structure; this contrasts with earlier work that has only produced comparable variation through heterogeneity in connectivity or degree distribution (Holland and Hastings 2008;Gilarranz and Bascompte 2012), differences in dispersal among species (de Roos et al 1998), or alteration of community dynamics in more complex models (Marleau et al 2014;Hata et al 2014). The appearance of this striking range of dynamical variation, both in the frequency and and quality of asynchrony among metacommunities shows the important role of the pattern of connections among local communities in shaping the regional dynamics of metacommunities.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…We further illustrate that differences in the pattern of connections and initial conditions among communities lead to the emergence of a wide array of stable asynchronous dynamics, leading to substantial differences in the potential persistence of an unstable predator-prey interaction at both the regional metacommunity and local patch level, despite the otherwise strict homogeneity of our metacommunities in which each community is identical and connected to exactly four other community patches. Our study is the first to produce this range of dynamical variation as a result of such subtle changes in spatial structure; this contrasts with earlier work that has only produced comparable variation through heterogeneity in connectivity or degree distribution (Holland and Hastings 2008;Gilarranz and Bascompte 2012), differences in dispersal among species (de Roos et al 1998), or alteration of community dynamics in more complex models (Marleau et al 2014;Hata et al 2014). The appearance of this striking range of dynamical variation, both in the frequency and and quality of asynchrony among metacommunities shows the important role of the pattern of connections among local communities in shaping the regional dynamics of metacommunities.…”
Section: Discussioncontrasting
confidence: 82%
“…This is an important step to better understanding how metacommunity dynamics are influenced by spatial structure given the focus on connectivity in the literature (Bunn et al 2000;Marleau et al 2014;Plitzko and Drossel 2015;Saunders et al 1991;Taylor et al 1993). We further illustrate that differences in the pattern of connections and initial conditions among communities lead to the emergence of a wide array of stable asynchronous dynamics, leading to substantial differences in the potential persistence of an unstable predator-prey interaction at both the regional metacommunity and local patch level, despite the otherwise strict homogeneity of our metacommunities in which each community is identical and connected to exactly four other community patches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those cases, hierarchically structured dispersal rates would actually act to suppress spatial patterns. More complex models have suggested that spatial coupling at other trophic levels or even with nutrients can lead to spatial patterning (Koelle and Vandermeer 2005;Marleau et al 2010Marleau et al , 2014, as adding additional species may shift which species are acting as activators or inhibitors. In systems with more than two species, the activator-inhibitor paradigm can be generalized to talk about sets of activators and inhibitors (Della Rossa et al 2012), but this still leaves the question, where in a food web do we expect to find activators or inhibitors, and therefore which dispersal structures can act to spatially stabilize ecosystems?…”
Section: Introductionmentioning
confidence: 99%
“…Perimeter:area ratio is especially important for islands that receive food web subsidies, with smaller islands having a greater per unit area effect of the subsidy. Each of these variables illustrates the importance of landscape ecology for understanding food web dynamics, a viewpoint that Polis pioneered decades ago and that continues to frame many research programs today (Marleau et al, 2014;Massol et al, 2011;.…”
Section: Accepted Manuscriptmentioning
confidence: 99%